2000
DOI: 10.1007/s002230001134
|View full text |Cite
|
Sign up to set email alerts
|

Bioglass ®45S5 Stimulates Osteoblast Turnover and Enhances Bone Formation In Vitro: Implications and Applications for Bone Tissue Engineering

Abstract: We investigated the concept of using bioactive substrates as templates for in vitro synthesis of bone tissue for transplantation by assessing the osteogenic potential of a melt-derived bioactive glass ceramic (Bioglass 45S5) in vitro. Bioactive glass ceramic and bioinert (plastic) substrates were seeded with human primary osteoblasts and evaluated after 2, 6, and 12 days. Flow cytometric analysis of the cell cycle suggested that the bioactive glass-ceramic substrate induced osteoblast proliferation, as indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
485
3
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 673 publications
(521 citation statements)
references
References 28 publications
23
485
3
10
Order By: Relevance
“…5). The stimulatory and dose-dependent osteogenic effects of these 22 ionic products have been well-documented in a number of studies [10,53,54,55] shown to increase the bone mineral density in both men and premenopausal women [60,61]. formation observed in the present study.…”
supporting
confidence: 80%
“…5). The stimulatory and dose-dependent osteogenic effects of these 22 ionic products have been well-documented in a number of studies [10,53,54,55] shown to increase the bone mineral density in both men and premenopausal women [60,61]. formation observed in the present study.…”
supporting
confidence: 80%
“…During the past three decades, however, the strategy in biomaterial research began to shift from developing biomaterials with a bio-inert tissue response to producing bioactive components that could elicit a controlled action and reaction in the physiological environment [1]. Since the late 1990's and the beginning of the new millennium, great potential has been attributed to the application of bioactive glasses in tissue engineering and regenerative medicine [39][40][41][42][43]. Bone tissue engineering is one of the most exciting future clinical applications of bioactive glasses.…”
Section: Figurementioning
confidence: 99%
“…Key mechanisms leading to enhanced new bone growth are now known to be related to the controlled release of ionic dissolution products from the degrading bioactive glass, especially critical concentrations of biologically active, soluble silica and calcium ions [8,191]. Recent studies have shown that bioactive (partially) resorbable glasses and their ionic dissolution products enhance osteogenesis by regulating osteoblast proliferation, differentiation, and gene expression [7,41,51,[191][192][193][194][195][196][197][198].…”
Section: Ion Dissolution From Bioactive Glasses: Genetic Control Of Omentioning
confidence: 99%
“…Indeed, numerous in vivo and in vitro studies have shown that 45S5 Bioglass ® can stimulate bone regeneration (Bosetti et al 2003;Gough et al 2004;Livingston et al 2002;Loty et al 2001;Tsigkou et al 2007;Xynos et al 2000). As a result, Bioglass ® is said to be both osteoproductive and osteoconductive.…”
Section: Introductionmentioning
confidence: 99%